2016
DOI: 10.1152/ajpcell.00034.2016
|View full text |Cite
|
Sign up to set email alerts
|

Changing calcium: CRAC channel (STIM and Orai) expression, splicing, and posttranslational modifiers

Abstract: A wide variety of cellular function depends on the dynamics of intracellular Ca(2+) signals. Especially for relatively slow and lasting processes such as gene expression, cell proliferation, and often migration, cells rely on the store-operated Ca(2+) entry (SOCE) pathway, which is particularly prominent in immune cells. SOCE is initiated by the sensor proteins (STIM1, STIM2) located within the endoplasmic reticulum (ER) registering the Ca(2+) concentration within the ER, and upon its depletion, cluster and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 97 publications
0
27
0
1
Order By: Relevance
“…[H3] Activity remodelling Ca 2+ sensitive tumour promoting pathways could be effected even in the absence of altered expression of Ca 2+ channels and pumps by the array of mechanisms regulating the activity of calcium channels and pumps, including activity regulating proteins (e.g. STIM1), post-translational modifications, splicing and trafficking 36,[51][52][53][54][55] . For example the proteolytic cleavage of some Ca 2+ channels and pumps can yield either inactive or more active forms [56][57][58][59] , and in the case of proteolytic cleavage of CaV1.2 can produce a C-terminal fragment that acts as a transcription factor 54 .…”
Section: [H3] Expression Remodellingmentioning
confidence: 99%
“…[H3] Activity remodelling Ca 2+ sensitive tumour promoting pathways could be effected even in the absence of altered expression of Ca 2+ channels and pumps by the array of mechanisms regulating the activity of calcium channels and pumps, including activity regulating proteins (e.g. STIM1), post-translational modifications, splicing and trafficking 36,[51][52][53][54][55] . For example the proteolytic cleavage of some Ca 2+ channels and pumps can yield either inactive or more active forms [56][57][58][59] , and in the case of proteolytic cleavage of CaV1.2 can produce a C-terminal fragment that acts as a transcription factor 54 .…”
Section: [H3] Expression Remodellingmentioning
confidence: 99%
“…) revealed that STIM‐mediated functions can be subject to complex physiological regulation, such as redox modulation and differential expression of protein variants (Bhardwaj et al . ; Niemeyer, ). The presence of two ORAI‐gating STIM isoforms allows a specialized regulation of physiological processes by a specific isoform.…”
Section: Ca2+ Signalling In Neutrophil Functionmentioning
confidence: 99%
“…STIM proteins are complex and multifaceted regulators of SOCE (Oh-Hora et al 2008;Soboloff et al 2012). The discoveries of functional STIM1 and STIM2 splice variants (Darbellay et al 2011;Miederer et al 2015;Rana et al 2015) and the identification of cysteine residues subject to oxidation (Hawkins et al 2010) revealed that STIM-mediated functions can be subject to complex physiological regulation, such as redox modulation and differential expression of protein variants (Bhardwaj et al 2016;Niemeyer, 2016). The presence of two ORAI-gating STIM isoforms allows a specialized regulation of physiological processes by a specific isoform.…”
mentioning
confidence: 99%
“…Furthermore, our ndings showing that NAC blocked both the translocation of this nuclear factor and upregulation of STIM1 and Orai1 suggest that these effects are related to ROS elevation. NFkB is a regulator of both STIM1 and Orai1 expression [26], and work done in mast cells and heterologous expression systems has demonstrated that binding of NFkB to speci c sites within the promoter regions of the STIM1 and Orai1 genes increases the transcription of their mRNAs [27].…”
Section: Stim1mentioning
confidence: 99%